Income Taxes and the Mobility of the Rich: Evidence from US and UK Households in Switzerland - Marko Köthenbürger; Costanza Naguib; Christian Stettler; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2023)
We provide quasi-experimental evidence on the income tax-induced migration of foreign high-income households living in Switzerland by exploiting the differential tax treatment of UK and US households. While the two groups are similar in terms of non-tax sorting preferences, US households are effectively insulated from Swiss income taxation due to the US world-wide income tax system. Comparing the location choices of UK households (our treatment group) with those of US households (our control group) within a one-hour commuting zone of Zurich, we find a migration elasticity with respect to the net-of-tax rate of around eight. This estimate mirrors the possibility of unrestricted migration between small Swiss municipalities with significantly different income tax rates.
Keywords: H24; H71; J44; R32; 330; high-income households; location choice; income taxes; sorting